2011
DOI: 10.1089/fpd.2010.0670
|View full text |Cite
|
Sign up to set email alerts
|

Raw-Fish-Eating Behavior and Fishborne Zoonotic Trematode Infection in People of Northern Vietnam

Abstract: Raw fish consumption in restaurants, for example, Sashimi style, is popular worldwide. In Vietnam, raw fish dishes are also traditionally prepared and consumed in private households. However, the habits of eating raw or otherwise inadequately cooked fish can be associated with risks of acquiring fishborne zoonotic trematode (FZT) infection. The present study was done in a fish-farming community in Nam Dinh, Vietnam, to obtain information about habits of eating raw fish dishes and risks for human FZT infection.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 10 publications
3
40
0
1
Order By: Relevance
“…In this model we found that previous infection (representing risk behavior) was a significant risk factor for reinfection, whereas male gender and increasing age were not. This indicates that the seemingly close association between male gender, increasing age and reinfection we observed (crude numbers), is possibly confounded by risk behavior of eating raw fish, a tradition mostly common among men [27].…”
Section: Discussionmentioning
confidence: 62%
“…In this model we found that previous infection (representing risk behavior) was a significant risk factor for reinfection, whereas male gender and increasing age were not. This indicates that the seemingly close association between male gender, increasing age and reinfection we observed (crude numbers), is possibly confounded by risk behavior of eating raw fish, a tradition mostly common among men [27].…”
Section: Discussionmentioning
confidence: 62%
“…In general, intestinal flukes cause less severe pathology in humans (Toledo et al 2006), but have become increasingly important because of food safety requirements (Chai et al 2005). Therefore, and also considering the life-cycle of FZTs that involves primary intermediate snail hosts, secondary intermediate fish hosts and final hosts like humans, pigs, dogs, cats, or fish-eating birds (Anh et al 2010;Dung et al 2010;Lan Anh et al 2009;Phan et al 2010a;Phan et al 2011), intervention targeting the fish host in aquaculture settings might be an effective strategy.…”
Section: Introductionmentioning
confidence: 99%
“…In northern Vietnam, common fish species used to prepare raw fish dish, also called "gỏi cá", are silver carp (Hypophthalmichthys molitrix), grass carp (Ctenopharyngodon idellus), rohu (Labeo rohita), and mrigal (Cirrhinus mrigala) (Chi et al 2009;Phan et al 2011). In the rural areas, slices of raw fish are soaked twice in a mild saline (1-3% NaCl) solution, before mixed with rice powder and eaten with herbs and sauce (Chi et al 2009;Phan et al 2011). Mostly adult men eat raw fish, whereas women mainly eat herbs dipped into the sauce.…”
Section: The Major Risk Factors In Human Infectionsmentioning
confidence: 99%
“…Children also have meals together with those eating raw fish, but the children consumed other types of food. In these places 32.2% of fish farm household members were infected with FZT (Phan et al 2011). In restaurants, raw fish is prepared in two different ways, i.e.…”
Section: The Major Risk Factors In Human Infectionsmentioning
confidence: 99%